Classificatory struggles in the midst of austerity: Policing or politics?. Issue 1 (January 2020) - Jeffery, Bob; Thomas, Peter; Devine, Dawn
This article reports findings on class identities amongst a small sample of mainly working-class residents in the City of Salford. We attempt to develop a Rancièrian framework for understanding class identities, centred on his key concept of dissensus, and how these ideas have been developed by Imogen Tyler through the notion of 'classificatory struggles'. From this, we identify a continuum of responses that are discernible in relation to the neoliberal order of classifications: from those orientated to a 'policing' function, either accepting and internalising dominant discourses or attempting to displace abjection onto others, to those that tend more towards 'politics' in either asserting alternative circuits of value or through an appeal to the name of the proletariat as a political claim to radical equality. In examining our data, we note that although a majority disavowed an explicit working-class identity, they nonetheless engaged in a range of classificatory struggles.